THE RELATIONSHIP OF WORK STRESS ON DRIVER PERFORMANCE - Suryani, Iza; David, Lucinda (DIVERSITY Logic Journal Multidisciplinary, 2024)
Background. Stress at work is a serious problem for the company because can reduce employee performance and the company. Research Purpose. This research aimed to determine and partially analyze the relationship between work stress and the performance of CV employees. Research Method. The sample in this study was the entire existing population and the sampling was taken by census which is a hundred percent of the total population as many as 22 respondents. This research was conducted in company, companies operating in the field of transportation and driver services in 2023. Data collection used questionnaires. Findings. Hypothesis testing using (t-test) between the work stress variable and employee performance variables shows the t value = -3.824 with a significant value of 0.001. By using the significance limit ÿ = 0.05, the t table is 2.068. From these results, the test criteria are -t count < -t table, namely -3.842 < -2.068, which means Ho is accepted and Ha is rejected. Conclusion. The work stress variable has a negative and significant influence on employee performance.